OPTIMALISASI MEDIA INFORMASI DALAM MENINGKATKAN LAYANAN CALON JEMAAH HAJI DI KEMENTERIAN AGAMA KABUPATEN SUKABUMI - Dalilah Husna Maulida; Aqila Qisty; Muhamad Ridwan; Eki Agustin; Latif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of Hajj services is a form of public service that requires an effective and efficient information system. However, in practice, several challenges are still encountered in delivering information to prospective Hajj pilgrims, such as limited access, lack of information updates, and low digital literacy among some communities. This study aims to analyze the optimization of information media in improving services for prospective Hajj pilgrims at the Ministry of Religious Affairs of Sukabumi Regency. This research employs a qualitative approach with a descriptive research design. Data collection techniques include observation, interviews, and documentation. The results indicate that the use of digital-based information media such as websites and social media has improved the effectiveness and efficiency of services. Nevertheless, challenges remain, including limited digital literacy, internet accessibility issues, and irregular information updates. Therefore, optimization strategies are needed, such as enhancing human resource competencies, developing integrated information systems, and combining digital and conventional media to improve service quality for prospective Hajj pilgrims.